Terapi Musik Suara Alam Sebagai Intervensi Kecemasan Pada Pasien Pre Operasi - Budiarti, Astrida; Rinasari, Galuh Mei; Faridah (Jurnal Keperawatan Muhammadiyah, 2025)
Background: Preoperative anxiety is a common issue that can affect patients' physiological and psychological conditions prior to surgery. Non-pharmacological interventions such as music therapy can serve as an alternative to reduce anxiety. Objective: This study aimed to analyze the effectiveness of nature sound music therapy in reducing preoperative anxiety among patients in the premedication room. Methods: A quasi-experimental design with a randomized pretest-posttest approach was used. A total of 48 respondents were selected through purposive sampling and divided into two groups: intervention and control. The Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire was used as the instrument. Data were analyzed using the Mann-Whitney test with a significance level of < 0.05. Results: The results showed that nature sound music therapy was effective in reducing the level of preoperative anxiety in the premedication room (ρ = 0.000 < α = 0.05). Conclusion: Nature sound music therapy provides a relaxing effect and significantly reduces preoperative anxiety. This therapy is recommended as a non-pharmacological intervention in premedication rooms to help manage patient anxiety.